IMPLEMENTATION OF GALLERY WALK IN COOPERATIVE LEARNING TO IMPROVE HIGH SCHOOL STUDENTS' MOTIVATION AND LEARNING OUTCOMES - Adibba, Aulya; Gunadi, Farid (Jurnal PTK dan Pendidikan, 2025)
Abstract High school students often experience low motivation and suboptimal achievement in mathematics learning, particularly in the topic of sequences and series. This condition underscores the need for instructional strategies that can enhance students’ engagement and conceptual understanding. This study aims to examine the effect of Gallery Walk–based cooperative learning on students’ learning motivation and achievement in mathematics among Grade X students at SMAN 1 Indramayu. The research employed Classroom Action Research, with students of class X–9 serving as the research subjects. Data were collected through motivation questionnaires, learning achievement tests, and classroom observations, and were analyzed using descriptive qualitative and quantitative methods. The results indicate an improvement in students’ learning motivation, as reflected in increased participation, enthusiasm, and collaboration, as well as a significant improvement in learning outcomes from Cycle I to Cycle II. These findings demonstrate that Gallery Walk–based cooperative learning is an effective pedagogical approach for fostering active learning environments and improving students’ understanding of mathematical concepts, thereby contributing to the enhancement of mathematics instruction at the secondary school level. Keywords: Cooperative Learning, Gallery Walk, Learning Motivation, Learning Outcomes, Sequences and Series.   Abstrak Siswa sekolah menengah sering mengalami rendahnya motivasi dan hasil belajar dalam pembelajaran matematika, khususnya pada materi barisan dan deret. Kondisi ini menunjukkan perlunya strategi pembelajaran yang mampu meningkatkan pemahaman dan keterlibatan siswa secara aktif. Tujuan penelitian ini adalah untuk mengetahui pengaruh penerapan Cooperative Learning berbasis Gallery Walk terhadap motivasi dan hasil belajar siswa kelas X SMAN 1 Indramayu. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) dengan subjek siswa kelas X-9. Data dikumpulkan melalui observasi, tes hasil belajar, dan angket motivasi, kemudian dianalisis secara deskriptif kualitatif dan kuantitatif. Hasil penelitian menunjukkan adanya peningkatan motivasi yang ditandai dengan keterlibatan, antusiasme, dan kerja sama siswa, serta peningkatan hasil belajar secara signifikan dari siklus I ke siklus II. Metode ini membantu guru menciptakan pembelajaran yang lebih interaktif dan membantu siswa memahami konsep matematika secara lebih mendalam. Kata Kunci: Cooperative Learning, Gallery Walk. Motivasi Belajar, Hasil Belajar, Barisan dan Deret.